Phytochemical Content Analysis Of Moringa Seed (Moringa Oleifera, L) Maceration Method - Leny Fitriah; Renda Suri Pratimi (Journal of Multidisciplinary Science, 2022)
Moringa is one of the plants used in traditional medicine by the community as an efficacious medicine utilizing all parts of the plant. Moringa seeds are part of the plant that can be used in medicine. A phytochemical test is a qualitative test of the chemical compound content of secondary metabolites, which is an essential first step in research on medicinal plants or in the search for new active compounds derived from natural materials that can be precursors for the synthesis of new drugs or become prototypes of certain active compounds. This research aimed to identify chemical compounds in Moringa seeds (Moringa oleifera, L). This research used the maceration method with 80% methanol solvent and hexane solvent, then identifying secondary metabolites was carried out by phytochemical test. The results showed that the phytochemical test results on the seed extract using the maceration method were alkaloids, flavonoids, and saponins. The results also showed that the seed sample had a moisture content below 10%, which was 9.36%.